Development of phenylpropanoid sucrose esters (PSEs) as lead drug candidates for alpha glucosidase inhibition - Devaraj, Surabhi (2017)
This research work focuses on the development of Phenylpropanoid Sucrose Esters (PSEs) as lead antidiabetic Alpha Glucosidase Inhibitors (AGIs) with the ultimate aim of eliminating the side effects associated with the current commercial drugs (Acarbose, Miglitol and Voglibose). Structure Activity Relationship (SAR) studies (in vitro, in silico and in vivo) have been used to guide this aim. In vitro inhibition studies indicate that most of our PSEs (feruloyl, coumaroyl and cinnamoyl) are much better than the standard drug Acarbose in inhibiting α-glucosidase. The IC50 values for the most active PSEs range from 4 to 9μM as compared to 328μM for Acarbose. Most of the PSEs examined show less inhibition of α-amylase in comparison to Acarbose and the most active PSEs have IC50 values comparable to Acarbose (0.7-2μM for the PSEs and 5μM for Acarbose). This indicates a greater selectivity of the PSEs towards α-glucosidase than α-amylase. This selectivity is thought to play important role in reducing the GI side effects that accompany the AGIs. From the in vitro studies, we can conclude that the type, position and number of phenylpropanoid substituents on the sucrose core, the aromatic ‘OH’ group, and the diisopropylidene rings greatly affect the anti-diabetic activity of the PSEs. Molecular docking studies of the PSEs show excellent correlation with the experimental data. From the binding mode pictures, we can conclude that the presence of free ‘OH’ groups on the aromatic substituents and the substitution at position 3 on sucrose core are critical for inhibition. PSEs dock close to the active site of α-glucosidase. Docking with α-amylase indicate multiple binding sites. PSEs where all four substituent groups interact with the amino acid residues at the catalytic site show a higher inhibition. Inhibition kinetic studies of all PSEs show mixed inhibition of the enzyme, α-glucosidase. All of the PSEs show a mixed partial type of inhibition of α-amylase except PSE 4FI (uncompetitive). One lead drug, PSE 4FI was selected to test its ability to mitigate post prandial hyperglycemia in vivo. Administration of the drug orally with starch is seen to reduce the increase in blood glucose levels following an oral starch tolerance test in STZ treated mice. PSE 4FI is as effective as Acarbose in reducing the surge in blood glucose after a starch load in the test mice. Further SAR studies were conducted with newly synthesized PSEs to identify the characteristics of the ideal PSE AGI. We conclude that the structural features essential to the anti-diabetic activity of the PSEs are found to be: four substituents on the sucrose core, alkenyl C=C, phenyl ring, diisopropylidene ring and the aromatic ‘OH’ groups. The most effective hydroxycinnamic acid substituents are the feruloyl and the caffeoyl moieties.